TUXUMDON KISTALARI VA ULARNING TURLARI. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Ovarian cysts are fluid-filled sacs that develop within or on the surface of the ovaries and are commonly observed in women of reproductive age [1, 2]. They may be classified as functional or pathological. Functional cysts, including follicular and corpus luteum cysts, are associated with the normal menstrual cycle and often resolve spontaneously without treatment [3]. Pathological cysts, such as dermoid cysts, endometriomas, and cystadenomas, may require medical or surgical intervention depending on their size and clinical presentation [4]. Clinical manifestations range from asymptomatic cases to pelvic pain, menstrual irregularities, and hormonal imbalance [5]. Early diagnosis through ultrasound imaging and laboratory investigations plays a crucial role in preventing complications such as rupture, torsion, and infertility [6].